Implementation of the organizational development policy of the cooperative office of small and medium enterprises muara enim district - Mardiana Mardiana; Hardiyansyah Hardiyansyah; Nisma Aprini (Penerbit Jurnal Indonesia, 2023)
The purpose of this research is to find out and analyze the implementation of organizational development policies for the Muara Enim Regency Small and Medium Enterprises Cooperative Service and to find out and analyze what factors are obstacles in the organizational development of the Muara Enim Regency Small and Medium Enterprises Cooperative Service.. The results of this research can be explained, the implementation of organizational development policies for the Muara Enim Regency Small and Medium Enterprises Cooperative Service, seen from the objectives, organizational structure, leadership, work procedures mechanisms, is in the good category. Meanwhile, organizational development is seen from the relationship management and reward system with not good category. There are several inhibiting factors in implementing organizational development policies for the Muara Enim Regency Small and Medium Enterprises Cooperative Service, namely: Internal organizational factors, loss of orientation, lack of focus, unclear accountability and incompetence